KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS DESKRIPSI DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 1 V KOTO KP. DALAM KABUPATEN PADANG PARIAMAN - Fitria, Vici; Asri, Yasnur; Gani, Erizal (Universitas Negeri Padang, 2018)
ABSTRACTThis article is written to determine the correlation of reading comprehension skills to the skill of writing a text description of the seventh grade students of SMP Negeri 1 V Koto Kp. Dalam Kabupaten Padang Pariaman. This research is a quantitative research by using descriptive correlational design. The variables in this study, namely reading comprehension skills as a variable X and writing skills of description text as a variable Y. The research instruments are an objective test and test performance. This research data is the result score skill tests readingcomprehension and writing skills test score results of the description text. The test results was compared using t-test formula to determine the correlation of reading comprehension skills to the skill of writing a text description of the seventh grade students of SMP Negeri 1 V Koto Kp. Dalam Kabupaten Padang Pariaman. The are three results in this study. First, the reading comprehension skills of students of class VII SMP Negeri 1 V Koto Kp. Dalam Kabupaten PadangPariaman are in a good qualifying with an average value of 82.79. Second, the text description writing skills of students of class VII SMP Negeri 1 V Koto Kp. Dalam Kabupaten Padang Pariaman are in a good qualifying with an average of 82.11. Third, based on the t-test results, it was concluded that there is a correlation had been reading comprehension skills of the students' writing skills of description text class VII SMP Negeri 1 V Kto Kp. Dalam Kabupaten Padang Pariaman because table value <thitung (1.80 <3,13).Kata kunci: korelasi, membaca pemahaman, menulis, teks deskripsi